ELLIS, Nick C.; LARSEN-FREEMAN, Diane. (ed.) Language as a Complex Adaptive System. In: Language Learning, n. 59, Suppl. 1, Dezembro 2009, 275p. - da Silva, Leandra Fagundes; Rodrigues, Lisandra (Organon, 2011)
ELLIS, Nick C.; LARSEN-FREEMAN, Diane. (ed.) Language as aComplex Adaptive System. In: Language Learning, n. 59, Suppl. 1,Dezembro 2009, 275p. Resenhado por Leandra Fagundes da Silva e Lisandra Rutkoski Rodrigues